MOBILE-BASED MANAGEMENT INFORMATION SYSTEM FOR ARAFURU HOUSE MANAGEMENT - Dewi Kartika; Muhamad Alda (Jurnal Riset Informatika, 2025)
Operational management at Wisma Arafuru currently relies heavily on conventional methods utilizing manual ledger recording. This dependence on manual processes often leads to significant administrative challenges, such as inaccuracies in guest reservation data, slow administrative handling, and difficulties for managers in monitoring room availability and facility conditions in real-time. Therefore, this study aims to design and build a mobile-based Management Information System as a digital transformation solution to enhance the operational efficiency and effectiveness of Wisma Arafuru. The methodology applied in this research is Research and Development (R&D), utilizing the systematic Waterfall software development model. The development stages include requirement analysis conducted through observation and interviews, system and interface design, application implementation using the Flutter framework supported by a Firebase backend, and comprehensive system testing. The result of this research is a mobile application that integrates key features such as room inventory management, a digital booking system, facility monitoring, and simple financial reporting. Based on implementation test results, the system has proven capable of providing convenience for managers in monitoring all operational activities, minimizing data recording errors (human error), and accelerating service processes for guests compared to the previous manual system.